Performance of Aether Low-Cost Sensor Device for Air Pollution Measurements in Urban Environments. Accuracy Evaluation Applying the Air Quality Index (AQI) - Georgios C. Spyropoulos; Panagiotis T. Nastos; Konstantinos P. Moustris (Atmosphere, 2021)
Significant portions of European cities’ population are still exposed to levels of air pollution deemed harmful by the World Health Organization. Given the high impact of air pollution both on human health and the economy, numerous low-cost electrochemical sensor monitoring systems are being installed. The market is forced to develop new air quality monitoring systems to meet the needs of providing forecasting services based on advanced technologies and protocols that utilize certain characteristics such as high accuracy, real-time monitoring, daily and yearly statistics, data access from both experts and simple users with the use of low-cost equipment. In this study, conducted in Athens, Greece, a comparison is attempted between the findings from a low-cost electrochemical sensor device and those of a static, fixed site measurement monitoring station; this comparison is based on the data quality and Air Quality Index (AQI) concerning data accuracy and quality on adverse health effects due to air pollution. With regard to the prediction of different AQI intervals, TPR ranges from 35.2% up to 100.0%, FPR from 0.0% up to 36.1% and FNR from 0.0% up to 38.1%. The outcome of this study reveals flexible and affordable alternatives adopted during the evaluation and calibration of low-cost gas sensors for monitoring.